Fabrication of aromatic polyimide films derived from diisocyanate with fluorinated dianhydride - Najaa Mustaffa,; Kaneko, Tatsuo; Takada, Kenji; Dwivedi, Sumant; Nadhratun Naiim Mobarak, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The range of available structure combinations to synthesize polyimide (PI) makes it technically possible to have various universal methods of producing PI film. The molecular design, in which monomers used to synthesize PI are carefully selected to meet specific application requirements as it influenced the properties of PI films. This study aimed to outline the approach for film fabrication through the casting of highly organo-soluble polyimide derived from 4,4’-methylene diphenyl diisocyanate (MDI) with 4,4’-(hexafluoroisopropylidene) diphtalic anhydride (6FDA) in different heating treatments. The solution drop amount was tested in order to control the films colour uniformity. A flexible and less crystalline MDI-6FDA film with an average thickness of 93